Analysis of the Influence of Good Corporate Governance, Profitability, Price Earning Ratio, Operating Expenses and Operating Income on Corporate Social Responsibility in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2017-2021 - Liswan Rusman; Rosfianti M Yadasang; Umar (Universitas Muhammadiyah Palu, 2023)
The purpose of this research is to prove the influence of Good Corporate Governance, Profitability, Price Earnings Ratio, Operating Expenses and Operating Income on Corporate Social Responsibility partially and simultaneously. The type of research data used is descriptive quantitative data. While the data source used is secondary data obtained through the website www.idx.co.id. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sample was selected using a purposive sampling technique and obtained 40 companies with 200 research samples. The data analysis method used is descriptive statistics, classical assumption test, multiple linear regression analysis with four predictors and hypothesis testing using IBM SPSS Statistics version 24. The conclusion of this study shows that the good corporate governance variable partially has a positive and significant effect on corporate social responsibility. Profitability partially has a negative and significant effect on corporate social responsibility, price earnings ratio, partially has a significant negative effect on corporate social responsibility, operating expenses and operating income partially does not affect corporate social responsibility. While good corporate governance, profitability, price earning ratio, operating expenses and operating income simultaneously affect corporate social responsibility.